An Art Lover's Guide to Florence - Testa, Judith Anne, 1943- (Book collections on Project MUSE., 2012)
No city but Florence contains such an intense concentration of art produced in such a short span of time ... while most guidebooks offer only brief descriptions of a large number of works, with little discussion of the historical background, this guide gives perspective on the rich and brilliant art of the Florentine Renaissance. Concentrating on a number of the greatest works by such masters as Botticelli and Michelangelo, the author explains each piece in terms of what it meant to the people who produced it and for whom it was made ... -- Back cover.